Nitrogen fixing bacteria in the family Acetobacteraceae and their role in agriculture. (3rd March 2015) - Reis, Veronica Massena; Teixeira, Kátia Regina dos Santos
<x xml:space="preserve">Abstract</x> For centuries, the Acetobacteraceae is known as a family that harbors many species of organisms of biotechnological importance for industry. Nonetheless, since 1988 representatives of this family have also been described as nitrogen fixing bacteria able to plant growth promotion by a variety of mechanisms. Nitrogen fixation is a biological process that guarantees that the atmospheric N2 is incorporated into organic matter by several bacterial groups. Most representatives of this group, also known as diazotrophic, are generally associated with soil rhizosphere of many plants and also establishing a more specific association living inside roots, leaves, and others plants tissues as endophyte. Their roles as plant growth‐promoting microorganisms are generally related to increase in plant biomass, phosphate and other mineral solubilization, and plant pathogen control. Here, we report many of these plant growth‐promoting processes related to nitrogen fixing species already described in Acetobacteraceae family, especially Gluconacetobacter diazotrophicus and their importance to agriculture. In addition, a brief review of the state of art of the phylogenetics, main physiological and biochemical characteristics, molecular and functional genomic data of this group of Acetobacteraceae is presented.